The Significance of Suffering in Purifying the Faith of Believers Based on 1 Peter 1:6-7 - Situmorang, Wendy Efriduansyah; Halawa, Mewipandi; Oktavia, Kristin (the International Journal of Education, Theology, and Humanities, 2023)
Suffering is a feeling or a phase in which a person or group of people feels pain, difficulties and probems. In the history of Christianity, there have been many times when Christians have been persecuted by various parties, be it from the government or the surrounding environment. History record that in 64 Ad massive persecution was aimed at Christians led by Emperor Nero. However, it is not only history that, in fact, in today’s modern era, Christianity still receives persecution, suffering or pressure from vaiorus parties. In this study the authors used a descriptive method whih is a method to provide an overview of the state of an object in the present but based on existing facts then provide analysis and interpretation. This research aims to provide an understanding that in every problem, suffering and persecution is not to weaken the Christian faith, because true Christianity that can stand the test under any circumstances. So it can be concluded that suffering brings purity of faith in God and at the same time makes us more in a relationship with God.